Hyperthermia and doxorubicin release by Fol-LSMO nanoparticles induce apoptosis and autophagy in breast cancer cells - Kulkarni-Dwivedi, Neha; Patel, Pratikshkumar R.; Shravage, V. Bhupendra; Umrani, Rinku D.; Paknikar, Kishore M.; Jadhav, Sachin H. (Nanomedicine, 2022)
Background: Studies on the anticancer effects of lanthanum strontium manganese oxide (LSMO) nanoparticles (NPs)-mediated hyperthermia at cellular and molecular levels are scarce. Materials & methods: LSMO NPs conjugated with folic acid (Fol-LSMO NPs) were synthesized, followed by doxorubicin-loading (DoxFol-LSMO NPs), and their effects on breast cancer cells were investigated. Results: Hyperthermia (45 degrees C) and combination treatments exhibited the highest (similar to 95%) anticancer activity with increased oxidative stress. The involvement of intrinsic mitochondria-mediated apoptotic pathway and induction of autophagy was noted. Cellular and molecular evidence confirmed the crosstalk between apoptosis and autophagy, involving Beclin1, Bcl2 and Caspase-3 genes with free reactive oxygen species presence. Conclusion: The study confirmed hyperthermia and doxorubicin release by Fol-LSMO NPs induces apoptosis and autophagy in breast cancer cells.
Keywords: Apoptosis; Autophagy; Breast cancer; combination therapy; doxorubicin; Folic acid; hyperthermia; LSMO; MDA-MB231 cells; PEG